2015
DOI: 10.1063/1.4930979
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Fast Random Particle Mesh method for efficient prediction of tonal and broadband noises of a centrifugal fan unit

Abstract: In this study, efficient numerical method is proposed for predicting tonal and broadband noises of a centrifugal fan unit. The proposed method is based on Hybrid Computational Aero-Acoustic (H-CAA) techniques combined with Unsteady Fast Random Particle Mesh (U-FRPM) method. The U-FRPM method is developed by extending the FRPM method proposed by Ewert et al. and is utilized to synthesize turbulence flow field from unsteady RANS solutions. The H-CAA technique combined with U-FRPM method is applied to predict bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The divergence-free turbulence is coupled into a CAA domain by a sponge-layer technique. For centrifugal fans Heo et al [18] have applied the RPM method to time-periodic flow with cyclostationary turbulence. The synthetic fluctuations are used as sources in an acoustic analogy solved by a boundary element method.…”
Section: Introductionmentioning
confidence: 99%
“…The divergence-free turbulence is coupled into a CAA domain by a sponge-layer technique. For centrifugal fans Heo et al [18] have applied the RPM method to time-periodic flow with cyclostationary turbulence. The synthetic fluctuations are used as sources in an acoustic analogy solved by a boundary element method.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the subsequent detailed flow analysis and the optimization were carried out for the operating point where the P-Q curve and the resistance curve, which is mainly due to the heat changer, meet together. Aerodynamic noise due to fan-driven flow in the out-door unit is also predicted using the FW-H integral equation in Equation (3). The half-spherical shape of the FW-H integral surface was formed in the downstream direction.…”
Section: Validation Of Numerical Modelmentioning
confidence: 99%
“…These studies confirmed that the H-CAA method could be reliably used to predict the BPF noise of the fan unit. By extending these works, Heo et al developed an efficient numerical method for predicting broadband noises as well as tonal noise of a centrifugal fan [3]. The proposed method is based on the Unsteady Fast Random Particle Mesh (U-FRPM) method.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an attempt to combine the FRPM method with a URANS solution for improved broadband noise predictions called U-FRPM method was developed for a centrifugal fan noise problem [33]. However, the underlining acoustic formulation used in that work remains unclear.…”
Section: Introductionmentioning
confidence: 99%